Promoción turística y el desarrollo sociocultural en el cantón Echeandia año, 2019 - Villamar Muñoz, Génesis Mercedes (2020)
This research project was carried out with the purpose of promoting publicizing and disseminating the attractions that the Canton Echeandia possesses and this through a promotion plan that helps publicize these attractions, due to the lack of promotion they have not been these places are exploited or exploited, and for this the support of the municipal GAD authorities of the Canton Echeandia is also needed, but so far the municipality currently lacks a tourism department and that is why the owners of the attractions do not feel 100% support of the authorities towards their tourism projects, therefore this research project will help tourism and in the same way socio-cultural development. The type of research used was field and exploratory since it allowed us to feel the tourist failure existing in the Canton and the methodology applied was observation, so we could investigate enough information from other authors and reach a previas inquiry after an analysis and checking the different definitions. The instruments used were: surveys and interviews, which helped to identify the different needs and also if this project had the approval of the Echeandian people, they mostly agreed that the Canton be promoted along with its attractions since the Tourism is a major axis in the socio-cultural development economy of the countries. The promotion plan consisted of promoting the attractions through social networks, web pages and leaflets.